Role of home caregivers in assisting patients with autism spectrum disorder: An integrative review. (Research, Society and Development, 2021)
This study aims to search the literature for activities performed by family caregivers to people with autism spectrum disorder, pointing out their main difficulties. And it is important to encourage research on this theme, emphasizing the action of caregivers at home. This is an integrative review study of a qualitative nature, the search was carried out in the following databases: Latin American and Caribbean Literature in Health Sciences (LILACS); ScientificElectronic Library Online (SciELO) and Nursing Database (BDENF). The articles were collected from June to July 2021. The descriptors were used: “Caregivers; Home Care and Autistic Spectrum Disorder”, selected from the list of Health Sciences Descriptors (DECs). Criteria for exclusion and inclusion in the study were selected, leaving a quantitative of 9 researches used. The main activity performed in the care of patients with ASD is the responsibility of caregivers, being mostly composed of mothers of patients, male caregivers, performing activities regarded as assistants, which generates a work overload for family caregivers. It is concluded that it is necessary to promote health to these caregivers, as it was clear during the construction of the study that this community still lacks information about the diagnosis and treatment of ASD.